The Relevance of Ibn Taimiyyah's Thought to the Condition of the Indonesian Political System During the Administration of President Joko Widodo - Sherly Nur Azizah; Gonda Yumitro (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article examines the relevance of the thought of Ibn Taimiyyah to the contemporary political landscape of Indonesia during the tenure of President Joko Widodo. Ibn Taimiyyah, a prominent Islamic scholar and philosopher, is known for his extensive works on Islamic jurisprudence, governance, and political theory. This research is important and interesting because Indonesia is a country with a Muslim majority, where the country's political system will be linked with an Islamic perspective. The method used in writing is a qualitative description method with data collection techniques through search engines, namely Google Scholar and Harzing Publish or Perish to obtain literature sources relevant to the research article. The data analysis technique used to be classified based on keyword searches to get the results of a number of journals, documents, and articles related to the topic of the article. The author finds that Ibn Taimiyyah's ideas are relevant to the Indonesian political system during the reign of President Joko Widodo to be analyzed, namely the first, related to the leadership of President Joko Widodo in leading the Indonesian state. Second, related to public services provided by President Joko Widodo for Indonesian citizens. The findings shed light on the ways in which Ibn Taimiyyah's ideas can inform contemporary debates surrounding governance, leadership, and state-society relations in Indonesia. This research contributes to a deeper understanding of the intellectual heritage of Islamic political thought and its implications for modern governance systems, particularly within the Indonesian context.